2021
DOI: 10.5999/aps.2020.01326
|View full text |Cite
|
Sign up to set email alerts
|

Closure of meningomyelocele defects using various types of keystone-design perforator island flaps

Abstract: Background Various methods have been described to close large meningomyelocele defects, but no technique has been proven superior to others. This study presents cases of meningomyelocele defect closure with a keystone-design perforator island flap.Methods A retrospective study was performed on 14 patients with meningomyelocele defects closed using various types of keystone flaps.Results The median age of the patients at surgery was 10.5 days (range, 1–369 days) and the average defect size was 22.5 cm2 (range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
(60 reference statements)
1
10
0
Order By: Relevance
“…We found that our surgical practice regarding the surgical line closure was matched with other studies 17–19 . Other study that recommends placing the midline skin scare on the repaired dura depended on the fascial turnover flap with or without the muscle.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We found that our surgical practice regarding the surgical line closure was matched with other studies 17–19 . Other study that recommends placing the midline skin scare on the repaired dura depended on the fascial turnover flap with or without the muscle.…”
Section: Discussionsupporting
confidence: 65%
“…We found that our surgical practice regarding the surgical line closure was matched with other studies. [17][18][19] Other study that recommends placing the midline skin scare on the repaired dura depended on the fascial turnover flap with or without the muscle. This technique allows no skin flap elevation, only skin undermining, so there will be no other placing for skin closure anywhere away from the midline.…”
Section: Discussionmentioning
confidence: 99%
“…40 Some studies have noted that the main limitation of primary closure is the actual size of the defect, but it is often the amount of surrounding redundant tissue that dictates plastic surgery consultation. 5,30 However, the average defect size closed primarily in the upper back was more than twice as large as the average defect closed primarily in the lumbar and lumbroscaral levels. Moreover, the redundant tissue of the upper back also likely contributed to the success of numerous other closure options, including random pattern and advancement flaps.…”
Section: Discussionmentioning
confidence: 99%
“…This was expected as MMCs most commonly affect the lumbrosacral levels of the posterior trunk, and the upper posterior trunk has much greater tissue laxity to facilitate primary closure by neurosurgeons 40 . Some studies have noted that the main limitation of primary closure is the actual size of the defect, but it is often the amount of surrounding redundant tissue that dictates plastic surgery consultation 5,30 . However, the average defect size closed primarily in the upper back was more than twice as large as the average defect closed primarily in the lumbar and lumbroscaral levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation